PENINGKATAN KOMPETENSI GURU DALAM MENDESAIN MULTIMEDIA INTERAKTIF DI SMAN 2 PALOPO - Irwan Ramli; Khaerati Khaerati; Nurasia Nurasia (Jurnal Abdi Insani, 2023)
The learning activities at SMAN 2 Palopo have not yet maximized by using of multimedia in the classroom learning process. Based on the results of interviews and observations at SMAN 2 Palopo, teachers only used PowerPoint downloaded from the internet and the teacher only made a few adjustments. This causes learning activities was not be able to attract students' attention. On the other hand, students spend a lot of time with smartphones. Observation results show that most students already have Android-based smartphones. This community service activity will increase the capacity of teachers in designing Android-based interactive multimedia. This multimedia allows students to access learning material via smartphone at anytime and anywhere. Implementation of the activity started with a focus group discussion (FGD) followed by a learning design workshop and Android-based interactive multimedia. This workshop was followed up with teacher assistance in designing interactive multimedia accompanied by the application of multimedia in the learning process. At the end of each lesson, reflection is carried out to see deficiencies in both the process and interactive multimedia. Based on the FGD activities carried out, teachers have never designed Android-based multimedia and do not have the competence to design Android-based multimedia. After going through a series of workshops and assistance with multimedia design, teachers were able to design Android-based interactive multimedia for use in learning. This assistance was carried out for four weeks for 4 meetings. The teacher stated that the ability to design multimedia has improved every week and hopes that this can continue. Based on the student response questionnaire, the multimedia used is easy to install and use, the appearance is attractive, and the material coverage is complete along with student worksheets. In this service activity, the teacher's ability to design Android-based interactive multimedia has increased, which has resulted in increased student learning activities in class.